2022
DOI: 10.1155/2022/4475245
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Undergraduate Students’ Waste Separation Behavior in the Environmentally Friendly Higher Education Mega Center of Guangzhou

Abstract: The volume of waste produced by aspects of both industrial life and daily life has increased in the past few years in conjunction with the rapidly growing economy in China. In urban areas, citizens consume more resources and produce much waste, which pollutes the environment. Many cities have proposed numerous regulations for waste separation to help build environmentally friendly cities. Plenty of studies tried to reveal the mechanism of residents’ waste separation behavior in different theoretical perspectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…Moreover, a questionnaire survey of undergraduate students at the higher education mega center of Guangzhou showed that environmental awareness, personal responsibility, convenience, and economic cost had a significant positive effect on waste separation behavior [34]. The attitudes, situational factors, publicity, and education are justified as the main factors influencing students' willingness to separate waste through a survey of 16 universities in Chongqing [17].…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Moreover, a questionnaire survey of undergraduate students at the higher education mega center of Guangzhou showed that environmental awareness, personal responsibility, convenience, and economic cost had a significant positive effect on waste separation behavior [34]. The attitudes, situational factors, publicity, and education are justified as the main factors influencing students' willingness to separate waste through a survey of 16 universities in Chongqing [17].…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Ecologically aware students may consider the environmental impact of 5G technology. They may be concerned about the energy consumption and carbon emissions associated with the infrastructure required to support 5G networks 50 . Environmental awareness can make students more conscious of electronic waste and the ecological consequences of increased electronic consumption.…”
Section: Literature Review With Hypothesis Developmentmentioning
confidence: 99%